Implementasi Pendidikan Inklusif di TK IT Nurul Ilmi - Salsabila Matondang; Ahmad Syukri Sitorus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the implementation of inclusive education at TK IT Nurul Ilmi as a form of the institution's commitment to upholding the right to education for children with special needs (ABK) in a general learning environment. This research uses a qualitative approach with a case study method. The results of the study show that Nurul Ilmi Islamic Kindergarten has opened access to education for children with special needs thru an adaptive and flexible learning approach, although it has not fully met all the indicators of inclusive education success comprehensively. The implementation of learning emphasizes the development of children's social skills by involving special companion teachers (GPK), supported by collaboration between teachers, school principals, parents, and professional staff. This study recommends the need to improve educators' competencies thru inclusion training, providing adequate resources, and strengthening institutional support to enhance the implementation of education.